Preparation method and application of lignin-based activated carbon adsorption material
The lignin-based activated carbon adsorption material prepared by direct activation/carbonization method solves the corrosiveness, volatility and high desorption energy consumption problems of existing CO2 capture materials, and achieves efficient and low-cost CO2 capture and waste resource recycling.
Patent Information
- Application Number
- CN202411757969.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-04
AI Technical Summary
The existing CO2 capture materials have problems such as corrosiveness, volatility, and instability. The desorption energy consumption is high and the cost is high, making it difficult to effectively capture low-concentration CO2.
Using lignin waste as raw materials, activated carbon adsorption materials with developed pores are prepared by direct activation/carbonization methods of activators such as KOH, K2CO3 and NaOH, mainly by physical adsorption and capture CO2.
It has achieved efficient CO2 capture, excellent adsorption performance, and the desorption process is carried out at a relatively mild temperature, saving energy consumption, reducing costs, and achieving efficient recycling of waste resource utilization.
Smart Images

Figure CN119551674A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon dioxide capture adsorbents, and relates to a method for preparing a CO2 porous carbon adsorbent using lignin waste as a raw material, and an application of the method in carbon dioxide capture. Background Art
[0002] Solving ecological and environmental problems such as global warming is a severe challenge facing mankind. It is recognized by the world that CO2 is the main greenhouse gas causing this phenomenon. Since the Industrial Revolution, the large-scale development and utilization of fossil fuels has brought strong impetus to the development of human society, promoted economic globalization and high-quality development, and at the same time, the concentration of CO2 in the atmosphere has gradually increased. According to data released by the World Meteorological Organization (WMO), the average concentration of CO2 in the atmosphere in 2022 reached 417.9ppm. Observations by the China Meteorological Administration showed that the average concentration of CO2 in China in 2022 was 419.3ppm, far higher than the average level of about 280ppm in the early industrial revolution. The International Panel on Climate Change (IPCC) predicts that if no intervention is made, by 2100, the average concentration of carbon dioxide in the atmosphere will reach 570ppm, and the average temperature during the same period will be about 3°C higher than before the industrial revolution. Therefore, it has become a global consensus to develop carbon capture technology and reduce carbon emissions.
[0003] The research of low-cost and high-efficiency carbon capture materials is the core of carbon capture technology. In the past decade, the research and development of CO2 capture materials has been very active. The materials that have been developed can be divided into alcohol amine solutions, metal oxides, activated carbon, metal organic frameworks (MOFs), zeolites, silica, solid amines, etc. Among them, ethanolamine (MEA) and its composite amine solutions are CO2 absorption materials that are currently widely demonstrated and promoted in industry. However, due to their corrosiveness, volatility and instability, they inevitably cause corrosion of operating equipment and loss of amines, and there are still many engineering problems that need to be solved. More importantly, ethanolamine (MEA) and its composite amine solutions have high regeneration energy consumption when desorbing carbon dioxide, generally higher than 2.7GJ / t CO2, and the cost is extremely high when applied to carbon capture of air and power plant flue gas. Metal oxides mainly adsorb carbon dioxide in the form of metal carbonates or bicarbonates, so they need to consume a lot of energy to release CO2. Activated carbon materials are widely studied. They mainly capture carbon dioxide by physical adsorption and are mostly used in pressure swing adsorption conditions. However, due to poor carbon dioxide adsorption selectivity, low adsorption capacity, and harsh operating conditions, they are not suitable for low-concentration air and power plant flue gas carbon capture. Metal organic frameworks are a type of metal-coordinated porous material that has emerged in recent years. Although MOFs have good adsorption performance for CO2, the cost of raw materials required for their preparation is generally high and the preparation process is relatively complicated. Currently, only BASF in Germany has promoted an industrial demonstration application of a MOF material.
[0004] Biomass activated carbon materials have always been a hot topic of research at home and abroad due to their adjustable pore structure and rich surface functional groups. Lignin is the main by-product of the papermaking industry. The world produces about 50 million tons of lignin waste through the papermaking industry each year, and the world produces 500 million to 3.6 billion tons of natural lignin each year. With the increasing severity of greenhouse effects such as global warming, research on CO2 capture activated carbon materials has focused on people's vision. The preparation of activated carbon usually includes carbonization and activation processes, and these two processes together promote the improvement of activated carbon performance.
[0005] The carbonization process mainly includes high-temperature carbonization, hydrothermal carbonization and steam thermal carbonization methods. The activation process includes physical activation (CO2, air, steam activator); chemical activation (alkali, acid, salt activator). Wang Rutao and others used waste lettuce leaves as raw materials, and prepared porous carbon by air drying, 600℃ argon pyrolysis, and KOH activation. The prepared porous carbon has a very high specific surface area of 3404m 2 / g and macropore volume 1.88cm 3 / g, and has excellent CO2 adsorption performance (Wang et al.ACSAppl.Mater.Interfaces.2012,4,5800–5806). Guo Yafei et al. used air, CO2, H3PO4 and NaOH as activators, and prepared porous activated carbon from sugarcane bagasse by carbonization followed by physical activation and chemical activation (Guo et al.Chemical Engineering Journal.2020,381,122736). This two-step carbonization and activation method is complicated and requires two high temperatures, which consumes a lot of energy. Serafin et al. used Amazon Andiroba shells as raw materials, first hydrothermally carbonized for 12 hours, and then used CO2 as an activator at 800°C for 1-10 hours to prepare porous activated carbon AND-AC-5h (Serafin et al. Journal of CO2 Utilization. 2022, 62, 102071). This preparation method takes a lot of time; Wu et al. used bamboo shoot shells as precursors, carbonized at 600°C and 700°C, and then activated with calcium chloride to obtain microporous carbonaceous adsorbents with different specific surface areas, different micropore / total pore volume ratios and CO2 adsorption performance (Wu et al. Journal of Analytical and Applied Pyrolysis. 2022, 168, 105742). The biomass raw materials used in the above preparation methods are less in nature and dispersed, the preparation steps are complicated, the preparation time is long, and the energy consumption is high.
[0006] Therefore, we urgently need an activated carbon adsorption material with low raw material price, abundant source, simple preparation method, low energy consumption and high CO2 adsorption performance. Summary of the invention
[0007] In view of the above-mentioned problems, the purpose of the present invention is to provide a method for preparing an activated carbon CO2 adsorbent using lignin waste and its application in carbon dioxide capture. The present invention uses lignin, the main waste of the papermaking industry, as raw material, and uses KOH, K2CO3 and NaOH as activators to prepare an activated carbon adsorbent material with developed pores and disorder by a simple direct activation / carbonization method. The activated carbon adsorbent material is mainly used to capture CO2 by physical adsorption using its rich pore structure and high specific surface area. The CO2 adsorption performance is high, and the adsorbent after use is desorbed at a relatively mild temperature, thereby achieving the purpose of efficient recycling of waste resources.
[0008] To achieve the above object, the present invention uses the following technical solutions:
[0009] On the one hand, the present invention provides a method for preparing a lignin-based activated carbon adsorption material, comprising preparing the lignin-based activated carbon adsorption material by a direct activation / carbonization method of an activator, deionized water and lignin.
[0010] In some embodiments, the preparation method comprises the following steps:
[0011] Step 1: Place the activator in a beaker;
[0012] Step 2: Add deionized water to the beaker in step 1 and stir;
[0013] Step 3: Add lignin to the solution in step 2 and stir;
[0014] Step 4: Evaporate the mixed solution of step 3 to dryness to obtain a solid;
[0015] Step 5: grinding the solid obtained in step 4 and calcining it under an inert atmosphere;
[0016] Step 6: Take out the solid from step 5 and grind it into powder;
[0017] Step 7: Dry the powder from step 6 to obtain a lignin-based activated carbon adsorption material.
[0018] In some embodiments,
[0019] In step 1, the activating agent is KOH, K2CO3 or NaOH;
[0020] In step 1, the amount of the activator is 0.5-5 g, preferably 0.5-2 g, more preferably 1 g;
[0021] In step 1, the specification of the beaker is 50-500 ml, preferably 50-200 ml, more preferably 100 ml.
[0022] In some embodiments,
[0023] In step 2, the amount of deionized water used is sufficient to fully dissolve the activator.
[0024] In some embodiments,
[0025] In step 2, the amount of deionized water is 20 to 60 ml, preferably 30 to 50 ml, more preferably 40 ml;
[0026] In step 2, the stirring time is 15 min to 60 min, preferably 20 min to 40 min, and more preferably 30 min.
[0027] In some embodiments,
[0028] In step 3, the amount of lignin used is 1-8 g, preferably 2-5 g, more preferably 3 g;
[0029] In step 3, the stirring time is 15 min to 60 min, preferably 20 min to 40 min, and more preferably 30 min.
[0030] In some embodiments,
[0031] In step 4, evaporating to dryness in an oil bath, a forced air drying oven or a vacuum drying oven, preferably a forced air drying oven, more preferably a vacuum drying oven;
[0032] In step 4, the evaporation temperature is 40 to 100° C., preferably 50 to 80° C., more preferably 60° C.;
[0033] In step 4, the evaporation time is 6 h to 24 h, preferably 8 h to 16 h, more preferably 12 h.
[0034] In some embodiments,
[0035] In step 5, calcining is carried out in a tube furnace or a muffle furnace, preferably a tube furnace;
[0036] In step 5, the inert atmosphere is nitrogen, argon, helium, neon or krypton;
[0037] In step 5, the calcination temperature is 200 to 1000° C., preferably 300 to 900° C., more preferably 750° C.;
[0038] In step 5, the calcination time is 10 min to 24 h, preferably 10 min to 12 h, more preferably 10 min to 6 h, and particularly preferably 1 h;
[0039] In step 5, the heating rate of calcination is 3-15°C / min, preferably 3-8°C / min, more preferably 5°C / min.
[0040] / min.
[0041] In some embodiments,
[0042] In step 6, the powder is washed with deionized water until it becomes neutral.
[0043] In another aspect, the present invention provides the use of the lignin-based activated carbon adsorption material prepared by the preparation method in carbon dioxide capture.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] (1) Most existing studies on biomass activated carbon are based on biomass with scarce and dispersed sources as raw materials. The present invention uses lignin, the main waste of the papermaking industry, to directly prepare activated carbon without purification. This lignin is widely available, low in price, concentrated in distribution, and contains rich functional groups.
[0046] (2) Most existing activated carbon preparation methods separate the carbonization process and the activation process. Such carbonization and activation methods are complicated and energy-intensive. The present invention directly activates / carbonizes lignin after impregnating it with KOH, K2CO3 and NaOH respectively. The steps are simple and only one high-temperature calcination is required, which saves a lot of time and energy.
[0047] (3) The lignin-based activated carbon adsorption material prepared by the present invention has well-developed and disordered pores. It utilizes its rich pore structure and high specific surface area to capture CO2 mainly through physical adsorption. The CO2 adsorption performance is high, and the adsorbent after use is desorbed at a relatively mild temperature, thereby achieving the purpose of efficient recycling of waste resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 SEM images of lignin (left a) and L-KOH-750℃ activated carbon adsorption material (right b);
[0049] Figure 2 It is the CO2 adsorption / desorption isotherm of L-KOH-750℃ activated carbon adsorption material at 25℃;
[0050] Figure 3 It is the CO2 adsorption / desorption isotherm of L-K2CO3-750℃ activated carbon adsorption material at 25℃;
[0051] Figure 4 This is the CO2 adsorption / desorption isotherm of L-NaOH-750℃ activated carbon adsorption material at 25℃. DETAILED DESCRIPTION
[0052] The above technical scheme of the present invention is specifically described below by way of examples. It is necessary to point out that the present examples are only used to further illustrate the present invention, but do not constitute any limitation to the present invention. Those skilled in the art may make some non-essential improvements and adjustments based on the content of the present invention.
[0053] Further, specifically, the preparation method of the lignin-based activated carbon adsorption material involved in the present invention is specifically described as follows:
[0054] Example 1 Preparation of L-KOH-750°C activated carbon adsorption material by direct activation / carbonization
[0055] Take 1g KOH in a 100ml beaker, add 40ml deionized water, stir with a magnetic stirrer for 30min, then add 3g lignin (lignin, abbreviated as L) and stir for 30min. Put it in a vacuum drying oven and dry it at 60℃ for 12h. After grinding the solid, put it in a tubular furnace, heat it to 750℃ at a heating rate of 5℃ / min under argon atmosphere, calcine it for 1h, then cool it naturally, take it out and grind it into powder, wash it with deionized water until it is neutral, and obtain L-KOH-750℃ activated carbon adsorption material after drying.
[0056] Example 2 Preparation of L-K2CO3-750℃ activated carbon adsorption material by direct activation / carbonization method
[0057] Take 1g K2CO3 in a 100ml beaker, add 40ml deionized water, stir with a magnetic stirrer for 30min, then add 3g lignin (L), and stir for 30min. Put it in a vacuum drying oven and dry it at 60℃ for 12h. After grinding the solid, put it in a tubular furnace, heat it to 750℃ at a heating rate of 5℃ / min under argon atmosphere, calcine it for 1h, then cool it naturally, take it out and grind it into powder, wash it with deionized water until it is neutral, and obtain L-K2CO3-750℃ activated carbon adsorption material after drying.
[0058] Example 3 Preparation of L-NaOH-750℃ activated carbon adsorption material by direct activation / carbonization method
[0059] Take 1g NaOH in a 100ml beaker, add 40ml deionized water, stir with a magnetic stirrer for 30min, then add 3g lignin (lignin, abbreviated as L) and stir for 30min. Put it in a vacuum drying oven and dry it at 60℃ for 12h. After grinding the solid, put it in a tubular furnace, heat it to 750℃ at a heating rate of 5℃ / min under argon atmosphere, calcine it for 1h, then cool it naturally, take it out and grind it into powder, wash it with deionized water until it is neutral, and obtain L-NaOH-750℃ activated carbon adsorption material after drying.
[0060] like Figure 1 As shown, compared with unmodified lignin, after activation / carbonization, rich and disordered pores are formed on the surface and inside of lignin, which increases the contact area with carbon dioxide and provides a large number of adsorption sites for CO2.
[0061] Example 4 CO2 adsorption test of lignin-based activated carbon adsorption material of the present invention
[0062] The CO2 adsorption / desorption isotherms of the lignin-based activated carbon adsorbent material of the present invention were tested using a fully automatic specific surface and porosity analyzer (Micromeritics ASAP 2460, USA) at an adsorption temperature of 25°C, a desorption temperature of 120°C, and 0-1 bar. The test results are as follows: Figure 2 , Figure 3 and Figure 4 shown.
[0063] like Figure 2 , Figure 3 and Figure 4 As shown in Figure 2, under the adsorption conditions of 25°C and 1 bar, the carbon dioxide adsorption capacity of the NaOH-activated lignin-based activated carbon adsorption material of the present invention reaches about 9 cm 3 / g, the carbon dioxide adsorption capacity of lignin-based activated carbon adsorption materials activated by KOH and K2CO3 meets the requirements of industrial applications and reaches about 70cm 3 / g, and the CO2 adsorbed by L-KOH-750℃ and L-K2CO3-750℃ was almost completely desorbed, showing an easy adsorption / desorption process. Therefore, the lignin-based activated carbon adsorption material prepared by the present invention has high CO2 adsorption performance, and the adsorbent after use is desorbed at a relatively mild temperature, achieving the purpose of efficient recycling of waste resources.
Claims
1. A method for preparing a lignin-based activated carbon adsorption material, characterized in that: The invention comprises preparing a lignin-based activated carbon adsorption material by directly activating / carbonizing an activator, deionized water and lignin.
2. The preparation method according to claim 1, characterized in that: The steps include: Step 1: Place the activator in a beaker; Step 2: Add deionized water to the beaker in step 1 and stir; Step 3: Add lignin to the solution in step 2 and stir; Step 4: Evaporate the mixed solution of step 3 to dryness to obtain a solid; Step 5: grinding the solid obtained in step 4 and calcining it under an inert atmosphere; Step 6: Take out the solid from step 5 and grind it into powder; Step 7: Dry the powder from step 6 to obtain a lignin-based activated carbon adsorption material.
3. The preparation method according to claim 2, characterized in that: In step 1, the activating agent is KOH, K2CO3 or NaOH; In step 1, the amount of the activator is 0.5-5g; In step 1, the beaker size is 50-500ml.
4. The preparation method according to claim 2, characterized in that: In step 2, the amount of deionized water used is sufficient to fully dissolve the activator.
5. The preparation method according to claim 2, characterized in that: In step 2, the amount of deionized water used is 20 to 60 ml; In step 2, the stirring time is 15 min to 60 min.
6. The preparation method according to claim 2, characterized in that: In step 3, the amount of lignin used is 1-8 g; In step 3, the stirring time is 15 min to 60 min.
7. The preparation method according to claim 2, characterized in that: In step 4, evaporating to dryness in an oil bath, a forced air drying oven or a vacuum drying oven; In step 4, the evaporation temperature is 40-100° C.; In step 4, the evaporation time is 6 h to 24 h.
8. The preparation method according to claim 2, characterized in that: In step 5, calcining in a tube furnace or a muffle furnace; In step 5, the inert atmosphere is nitrogen, argon, helium, neon or krypton; In step 5, the calcination temperature is 200 to 1000° C.; In step 5, the calcination time is 10 min to 24 h; In step 5, the heating rate of calcination is 3-15°C / min.
9. The preparation method according to claim 2, characterized in that: In step 6, the powder is washed with deionized water until it becomes neutral.
10. Use of a lignin-based activated carbon adsorption material prepared by the preparation method according to any one of claims 1 to 9 in carbon dioxide capture.